The gene YEF3 function encoding translation elongation factor eEF3 is partially conserved across fungi - Maldonado, Giovanna; García, Alejandra; Herrero, Saturnino; Castaño, Irene; Altmann, Michael; Fischer, Reinhard; Hernández, Greco (Frontiers in Microbiology, 2024)
Translation is a fundamental process of life. In eukaryotes, the elongation step of translation is highly conserved and is driven by eukaryotic translation elongation factors (eEF)1A and eEF2. A significant variation of the elongation is the activity of elongation factor eEF3 in Saccharomyces cerevisiae encoded by the gene YEF3 with orthologs in all fungal species, a few algae, and some protists. In S. cerevisiae, YEF3 is an essential gene and eEF3 plays a critical role in translation elongation, as it promotes binding of the ternary complex acylated-tRNA-eEF1A-GTP to the aminoacyl (A) site of the ribosome, the release of uncharged tRNAs after peptide translocation, and ribosome recycling. Even though YEF3 was discovered more than 40 years ago, eEF3 has been characterized almost exclusively in S. cerevisiae. We undertook an in vivo genetic approach to assess the functional conservation of eEF3 across phylogenetically distant fungal species. We show that eEF3 from Zygosaccharomyces rouxii and Candida glabrata (both belonging to phylum Ascomycota), Ustilago maydis (phylum Basidiomycota), and Gonapodya prolifera (phylum Monoblepharomycota), but not Aspergillus nidulans (phylum Ascomycota), support the growth of S. cerevisiae lacking the endogenous YEF3 gene. We also prove that eEF3 is an essential gene in the ascomycetes C. glabrata and A. nidulans, two species with huge medical value and relevant for genetic and metabolic studies, which opens the possibility of using eEF3 as a target to fight candidiasis.